# Simple Commutative Relation on Matrices ## Problem 55

Let $A$ and $B$ are $n \times n$ matrices with real entries.
Assume that $A+B$ is invertible. Then show that
$A(A+B)^{-1}B=B(A+B)^{-1}A.$

(University of California, Berkeley Qualifying Exam) Add to solve later

## Proof.

Let $P=A+B$. Then $B=P-A$.

Using these, we express the given expression in terms of only $A$ and $P$.
On one hand, we have
$A(A+B)^{-1}B=AP^{-1}(P-A)=AP^{-1}P-AP^{-1}A=A-AP^{-1}A.$ On the other hand we have
$B(A+B)^{-1}A=(P-A)P^{-1}A=PP^{-1}A-AP^{-1}A=A-AP^{-1}A.$ Thus these are equal.

This completes the proof.

## Comment.

Did I make a mistake? Isn’t it too simple to be a qualifying exam problem? Add to solve later

### More from my site

#### You may also like...

This site uses Akismet to reduce spam. Learn how your comment data is processed.

###### More in Linear Algebra ##### All the Eigenvectors of a Matrix Are Eigenvectors of Another Matrix

Let $A$ and $B$ be an $n \times n$ matrices. Suppose that all the eigenvalues of $A$ are distinct and...

Close